Investigation Of Standard Test Condition Requirement In Establishing Reliable Current-Voltage Characterization System For Dye –Sensitized Solar Cell (Dssc) As An Alternative For Commercial Solar Simulator And Photovoltaic Measurement System - Hafiz Hakimie, Mat Tahir (2022)
Nominal output characteristics of any fabricated solar cells or modules are conventionally evaluated based on standard requirement that is called as Standard Test Condition (STC). In order to comply with this STC requirement before products are being commercialized, each fabricated solar cell/module must undergo several tests such as current-voltage measurements under three environmental conditions: solar irradiance of 1000W/m2, cell temperature of 25°C and air mass (AM) of 1.5. Generally, xenon-based lamps are commonly utilized as main illumination source of 1000W/m2 and the term ‘AM1.5’ is mainly structured based on commercially-available glass-based AM1.5 filter in typical solar simulators. However, the detailed theories how and why all these requirements should or should not be structured is rarely discussed and revealed in the literatures. Therefore, this study will conduct deep investigation in developing proper and relevant methodologies so that the reliable current-voltage characterization system can be established by complying these STC requirements.